2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9629882
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias towards high and low caloric food on repeated visual food stimuli: An ERP study

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Previous studies in mixed‐gender samples have found increased ERP amplitudes for high calorie food (Duraisingam et al., 2021; Kirsten et al., 2022). In our study, for P4, low calorie stimuli elicited higher amplitudes than high calorie stimuli ‐ as well as descriptively also for Pz and P3 – suggesting a high motivational significance, reflected by valence ratings only in the AN group.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies in mixed‐gender samples have found increased ERP amplitudes for high calorie food (Duraisingam et al., 2021; Kirsten et al., 2022). In our study, for P4, low calorie stimuli elicited higher amplitudes than high calorie stimuli ‐ as well as descriptively also for Pz and P3 – suggesting a high motivational significance, reflected by valence ratings only in the AN group.…”
Section: Discussionmentioning
confidence: 90%